Ceftazidime-Avibactam Versus Colistin for the Treatment of Multidrug-Resistant Pseudomonas aeruginosa Infections: A Multicenter Cohort Study - Thamer A. Almangour; Zakiyah Alkherb; Leen Ghonem; Mohammed Al Musawa; Abdullah Almohaizeie; Sara Almuhisen; Aminah Alharbi; Nader Damfu; Doaa Aljefri; Jeelan Alghaith; Awaly Alfozan; Ahlam Alghamdi; et al. (Pharmaceuticals)
Purpose: To evaluate the real-world evidence of ceftazidime-avibactam (CAZ-AVI) compared to intravenous colistin for the treatment of multidrug-resistant (MDR) P. aeruginosa infections. Method: This is a multicenter, retrospective cohort study conducted in the period between 2017 and 2023 at five institutions for patients who received either CAZ-AVI or colistin-based regimens for treating MDR P. aeruginosa infections. Outcomes were compared using multivariate logistic regression analysis. Result: Among the screened patients, 203 patients were included: 89 in the CAZ-AVI group and 114 in the colistin group. A total of 57% presented with pneumonia, 21% with bacteremia, and 61% were in the intensive care unit. The rate of clinical cure was significantly higher among patients who received CAZ-AVI (67% vs. 50%; OR, 2.07; 95% CI, 1.16–3.68). The rate of in-hospital mortality was numerically lower among patients who received CAZ-AVI (40% vs. 49%; OR, 0.58; 95% CI, 0.33–1.03). The rate of AKI was significantly lower among patients who received CAZ-AVI (15% vs. 43%; OR, 0.23; 95% CI, 0.11–0.45). Conclusion: CAZ-AVI was more effective in treating MDR P. aeruginosa infections and showed a better safety profile compared to colistin. Thus, CAZ-AVI could be a better alternative for treating MDR P. aeruginosa infections.